Distributed quality-of-service routing in ad hoc networks. - Shigang Chen (IEEE Journal on selected areas in communications)
In an ad hoc network, all communication is done over wireless media, typically by radio through the air, without the help of wired base stations. Since direct communication is allowed only between adjacent nodes, distant nodes communicate over multiple hops. The quality-of-service (QoS) routing in an ad hoc network is difficult because the network topology may change constantly, and the available state information for routing is inherently imprecise. In this paper, we propose a distributed QoS routing scheme that selects a network path with sufficient resources to satisfy a certain delay (or bandwidth) requirement in a dynamic multihop mobile environment. The proposed algorithms work with imprecise state information. Multiple paths are searched in parallel to find the most qualified one. Fault-tolerance techniques are brought in for the maintenance of the routing paths when the nodes move, join, or leave the network. Our algorithms consider not only the QoS requirement, but also the cost optimality of the routing path to improve the overall network performance. Extensive simulations show that high call admission ratio and low-cost paths are achieved with modest routing overhead. The algorithms can tolerate a high degree of information imprecision